Hydrilla Stem Weevil: Bagous hydrillae O’Brien - Emma Weeks; Jim Cuda; Michael J. Grodowitz (EDIS, 2014)
Bagous hydrillae O’Brien is a semi-aquatic weevil that feeds on the aquatic invasive weed Hydrilla verticillata (L.f.) Royle. Larvae of the weevil mine hydrilla stems and the adults feed on the stems and submerged leaves. This weevil was discovered during overseas surveys for biological control agents for hydrilla during the 1980s and was first introduced to the U.S. in Florida in 1991 after extensive host-specificity testing. This 5-page fact sheet was written by Emma Weeks, Jim Cuda, and Michael J. Grodowitz, and published by the UF Department of Entomology and Nematology, June 2014.